Probing Effective Language Development Programs in Indonesian Islamic Higher Education: A Case of IAIN Pekalongan - Nur Kholis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Language development programs in higher education institutions have been facing concurring obstacles. A great part of these obstacles are caused by low proficiency level of students. The fact that prospective students are considered to have adequate experience in learning foreign language does not necessarily make the programs design undemanding. In order to cope with this challenge, higher education institutions need to perform thorough and careful processes of designing language development programs. This article argues that determining realistic goals, keeping up with latest research findings, and creating supportive environments will greatly contribute to effectiveness of these programs.